Effectiveness of Legislative Measures in Protecting Trees as Key Elements of Green Infrastructure - MOYZEOVÁ, Milena; PALAJ , Andrej (Journal of Ecohumanism, 2024)
The concept of green infrastructure is becoming increasingly central to both national and international research, particularly for its role in promoting ecological stability, protecting biodiversity, and supporting multifunctional land use and landscape diversity. In cultural landscapes, elements such as solitary trees, tree groups, and tree rows are integral components of green infrastructure, fulfilling essential ecological, aesthetic, cultural-historical, and landscape functions. Among these, protected trees are a critical element, serving as key indicators in comprehensive landscape-ecological assessments of urban environments. This paper aims to (i) evaluate the distribution and number of protected trees in Bratislava, the capital of Slovakia, and (ii) assess whether these trees meet the established criteria for protection. Additionally, we examined factors within the protection zones of these trees that may negatively impact their occurrence, vitality, and stability. The results are presented through graphical analysis and photographic documentation. Furthermore, the study includes findings from a sociological survey conducted via an online questionnaire with a sample of 514 respondents, highlighting the perceived importance of these trees in the urban environment.